A Study Of Human Resource Policies In National And Multinational Companies In The Malaysian Automobile Industry - Lee, Kok Hoon (2006)
This research profiles the satisfaction of HR policies among employees in three automobile manufacturing companies: Japanese, American and a national automobile producer.